Challenges of Non-English Teachers and Students’ Views on English Learning at SDN Cilaja 2 - Eti Nurcholisah; Chintia Mutiasari; Ghina Nurjannah; Risya Kamila; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
This study examines the challenges non-English teachers face and students' views on English learning at SDN Cilaja 2, an elementary school in a rural area of Banten Province, Indonesia. Using a qualitative descriptive method, data were collected through semi-structured interviews with three non-English teachers, and questionnaires were distributed to 52 students in grades IV and V. The results showed that the teachers experienced limitations in English language mastery, pedagogical competence, and availability of learning resources. Despite this, they try to engage students through basic strategies such as songs, games, and visual media. On the other hand, students are highly interested in English lessons, especially when learning activities are interactive and fun. However, many students find it challenging to understand the material and feel confused due to the limited teaching methods and the absence of exceptional teachers. The gap between students' motivation and their ability to understand lessons underscores the importance of the presence of competent English teachers and a better teaching approach in rural schools. This study concludes that effective English learning at the primary school level requires student motivation, teacher readiness, and a supportive learning environment. Therefore, it is recommended that the government place professional English teachers in primary schools and provide pedagogical training for non-specialist teachers to improve the quality of English language learning.